Dynamic network slice resources reconfiguration in heterogeneous mobility environments - Meneses, Flávio (2019)
This paper proposes a framework that optimizes network slicing provisioning in over‐the‐top (OTT) scenarios, by reducing occupied resources of slices from where the User Equipment (UE) handovers from. To achieve this, the framework leverages an existing Software Defined Networking (SDN)‐based UE virtualization scheme, which allows to instantiate in the cloud a representation of the physical device and its current connectivity context. This scheme was extended with the ability to anchor the UE's datapath and mask the underlying slices in a single end‐to‐end slice, allowing handover mechanisms between slices to become transparent to involved endpoints. This framework was implemented and evaluated in an experimental testbed where the UE moves between Wi‐Fi and long‐term evolution (LTE) slices, with results showing that upstream and downstream throughput is dynamically adapted to the UE requirements prior to the handover.